Associations of early sport specializationand high training volume with injury rates in National Collegiate Athletic Association Division I athletes - Ahlquist, B. S.; Cash, B. M.; Hame, S. L. (Orthopaedic Journal of Sports Medicine, 2020)
Background: There are 60 million US youth who participate in organized athletics, with large increases in both sport participation and specialization during the past 2 decades. There is some evidence that increased sport specialization and training volumes may be associated with increased injuries in adolescent populations. This study examines these variables in a population of elite college athletes. Hypothesis: Early sport specialization (ESS) and a high training volume are risk factors for injury and/or surgery in National Collegiate Athletic Association (NCAA) Division I athletes. Study Design: Cross-sectional study; Level of evidence, 3. Methods: All Division I athletes at a single institution were surveyed regarding demographics, scholarship status, reason for specialization, age at specialization, training volume, and injury history. Chi-square and Mann-Whitney U tests were performed to identify significant differences. Results: Athletes who specialized in their eventual varsity sport before age 14 years were more likely to report a history of injuries (86.9% vs 71.4%), multiple injuries (64.6% vs 48.8%), multiple college injuries (17.2% vs 6.0%), a greater number of total injuries (2.0 vs 1.0), and require more time out for an injury (15.2 vs 6.5 weeks) than those who did not. They were also more likely to be recruited (92.9% vs 82.1%) and receive a scholarship (82.8% vs 67.9%). Athletes who trained for greater than 28 hours per week in their eventual varsity sport before high school were more likely to report multiple injuries (90.0% vs 56.3%), multiple college injuries (40.0% vs 12.5%), a surgical injury (60.0% vs 22.9%), multiple surgical injuries (30.0% vs 4.7%), a greater number of total injuries (2.5 vs 2.0), and more time out for an injury (36.5 vs 11.0 weeks) than those who did not (all P < .05). However, these athletes were not more likely to be recruited (90.0% vs 89.8%) or receive a scholarship (80.0% vs 74.5%). Conclusion: CAA Division I athletes with ESS and/or a high training volume sustained more injuries and missed more time because of an injury, but those with ESS were more likely to be recruited and receive a college scholarship. This knowledge can help inform discussions and decision making among athletes, parents, coaches, trainers, and physicians.